GAMBARAN KUALITAS HIDUP PASIEN PENYALAHGUNA NARKOBA DENGAN METODE WHOQOOl SETELAH MENJALANKAN PROGRAM KONSELING DI KLINIK PRATAMA BNN KOTA CIMAHI. - Hana Gumiyarna (JURNAL KESEHATAN KARTIKA, 2021)
Background : In an effort to carry out a rehabilitation program, one of which is an assessment of the quality of life of a client, this assessment is carried out by assessing using an instrument called WHOQool Breef which was officially issued by WHO. This study aims to determine the description of the quality of life based on the physical, psychological, social relations and environmental domains based on the score using the WHOQool instrument. Method : This type of research is a qualitative descriptive observative design where the number of samples is 20 patients, which is the total population of the study. Data analysis in this study was carried out univariately with the results of data processing in the form of frequency distribution. Result : it is known that there is a change in the quality of life of patients in the physical domain where 20% is categorized as good, and 80% is categorized as sufficient. In the Psychological domain 90% is categorized as sufficient and 10% is still categorized as less. In the social relations domain 80% is still categorized as lacking but 20% is categorized as sufficient, while in the environmental domain 60% is categorized as lacking and 40% is categorized as sufficient.Conclusion : Rehabilitation programs through counseling therapy given to patients can basically provide measurable changes in quality of life based on the WHOQOOL instrument.